Ordinance No. A 236, §§ 1 (Pts. 1, 7, 12, 21, & 31), 9, 10, 26, 37, & 39, Yakima (a.k.a. North Yakima) City Council (1917) (Yakima, Washington). - (:unkn) unknown (My University, 1917)
Any person in said city, except police officers and other persons who are authorized by law or have obtained proper authority so to do from the Chief of Police of said city, who shall carry or wear in any manner concealed upon his or her person, any dirk, dagger, stilletto, bowie-knife, sword-cane, gun, pistol, revolver sling-shot, metal knuckles, or any other dangerous weapon or instrument which may be used to inflict injury upon the person of another. Any person in said city, except police officers and other persons whose duty it is to make arrestes, who shall draw, exhibit or attempt to use, any deadly weapon with intent to do bodily injury to another, or with the intention of intimidating such other person.-Any person in said city, except police officers engaged in the lawful discharge of their duty, and persons practicing at target shooting in a duly licensed shooting gallery, who shall fire off or discharge any gun, pistol or fire arm of any kind within the city limits...or who shall sell or give, or permit to be sold or given away to any person under the age of twenty one-years any intoxicating liquor, cigar, cigarette, cigarette paper or wrapping, or tobacco in any form; or who shall sell, or give, or permit to be sold or given to any person under the age of eighteen years, any revolver, or pistol
Keywords: BRANDISHING; CARRY - CONCEALED; DISCHARGE; TRANSFER - MINORS